Uzupełnij(chodzi o wyłączanie wspólnego czynnika przez nawias):
a)(a+b)x³+(a+b)x²+(a+b)x= (a+b)x(...........................................)
b)(x+1)x²+(x+1)(1-x)+(x+1)²=(x+1)(..........................................................)

Daję naj!!

3

Odpowiedzi

2010-03-13T21:51:27+01:00
A)(a+b)x³+(a+b)x²+(a+b)x= (a+b)x(x²+x+1)
b)(x+1)x²+(x+1)(1-x)+(x+1)²=(x+1)(x²+(1-x)+(x+1))=
(x+1)(x²+1-x+x+1)=(x+1)(x²+2)
Najlepsza Odpowiedź!
2010-03-13T21:52:49+01:00
B) (x+1)(x+1-x+x+1)
a)(a+b)x(x2+x+1)
2010-03-13T22:14:58+01:00
A)
(a+b)x(x²+x+1)
b)
(x+1)x²+(x+1)(1-x)+(x+1)²=(x+1)x²-x²+1+x²+1=(x+1)x²+2=(x+1)(x²+2)